Long and Short Term Cumulative Structural Priming Effects - Kaschak, Michael P. (Lang Cogn Neurosci, 2012)
We present six experiments that examine cumulative structural priming effects (i.e., structural priming effects that accumulate across many utterances). Of particular interest is whether (1) cumulative priming effects transfer across language production tasks and (2) the transfer of cumulative priming effects across tasks persists over the course of a week. Our data suggest that cumulative structural priming effects do transfer across language production tasks (e.g., from written stem completion to picture description, and from picture description to written stem completion), but only when both tasks are presented in the same experimental session. When cumulative priming effects are established in one task, and the second (changed) task is not presented until a week later, the cumulative priming effects are not observed.